Effect of the natural aging time on the age-hardening response and precipitation behavior of the Al-0.4Mg-1.0Si-(Sn) alloy. (15th January 2021) - Tu, Wenbin; Tang, Jianguo; Ye, Lingying; Cao, Lingfei; Zeng, Yu; Zhu, Qianqian; Zhang, Yong; Liu, Shengdan; Ma, Lehang; Lu, Jinkun; Yang, Bing
Abstract: The combined effect of adding Sn and natural aging (NA) time on the precipitation and age-hardening rate of the Al-0.4Mg-1.0Si alloy was investigated by a hardness test, electrical resistivity test, differential scanning calorimetry (DSC) analysis, 3-D atom probe (3DAP) analysis, and transmission electron microscopy (TEM). The results showed that the NA of the Al-0.4 Mg-1.0Si alloy was suppressed by adding Sn. This suppression was ascribed to the suppression of the formation of clusters. The short NA time (less than 5 days) had a positive effect on the subsequent artificial aging (AA) in the Sn-added alloys, i.e., a fast AA-hardening rate was achieved. The positive effect of the NA on the AA in the Sn-added alloys increased as the amount of Sn increased, but decreased as the NA time increased. The AA was negatively affected by the NA when the NA time was increased to 14 days. The accelerated AA precipitation of the Sn-added alloys after a short NA time was responsible for the fast AA-hardening rate. This accelerated precipitation was related to the increased amount of retained quenched-in vacancies according to their NA resistivity curves and similarity of the chemical composition between the Sn-containing clusters and β" phases. Graphical abstract: Unlabelled Image Highlights: Sn atoms can be incorporated into MgSi clusters to form Sn-containing clusters which have higher average Mg/Si ratio and size than that of the Sn-free clusters. The added Sn increase the concentration of vacancies of the as-quenched alloys. A short of NA time have positive effect on the subsequent AA in the Sn-added Al-0.4 Mg-1.0Si alloy. The Sn-containing clusters and more quenched-in vacancies retained in Al matrix are responsible for positive effect of 1 day NA on subsequent AA in the Sn-added Al-0.4 Mg-1.0Si alloy.